2015
DOI: 10.3920/wmj2014.1747
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins as antagonistic or supporting agents in the interaction between phytopathogenicFusarium andAlternaria fungi

Abstract: The role of mycotoxins in the microbial competition in an ecosystem or on the same host plant is still unclear. Therefore, a laboratory study was conducted to evaluate the influence of mycotoxins on growth and mycotoxin production of Fusarium and Alternaria fungi. Fusarium culmorum Fc13, Fusarium graminearum Fg23 and two Alternaria tenuissima isolates (At18 and At220) were incubated on wheat kernels supplemented with alternariol (AOH), tetramic acid derivates (TeA), deoxynivalenol (DON) and zearalenone (ZEA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Interactions between Alternaria and Fusarium species and consequently their impact on toxin production has been reported by Muller et al [25]. It was found that the increased population of Alternaria on ripening ears of wheat coincided with reduced population of Fusarium species [25,26]. Therefore, the increase of Alternaria toxins in cereals was often accompanied by the decline of Fusarium toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between Alternaria and Fusarium species and consequently their impact on toxin production has been reported by Muller et al [25]. It was found that the increased population of Alternaria on ripening ears of wheat coincided with reduced population of Fusarium species [25,26]. Therefore, the increase of Alternaria toxins in cereals was often accompanied by the decline of Fusarium toxins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the species of Alternaria alternata isolated from Argentinean wheat kernels could produce TeA, AOH and AME, but the species of Alternaria infectoria only produce TeA [24]. Interactions between Alternaria and Fusarium species and consequently their impact on toxin production has been reported by Muller et al [25]. It was found that the increased population of Alternaria on ripening ears of wheat coincided with reduced population of Fusarium species [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of fungi and bacteria with Alternaria could exist more often in competition and in antagonistic processes than in undisturbed coexistence. Few studies dealing with the co-occurrence of Fusarium and fluorescent pseudomonads with Alternaria suggest the implication of mycotoxins as antagonistic substances in these interactions [52,53] Simultaneously, competition processes between different fungal genera affect the production of mycotoxins or increase the metabolization of toxins [54,55]. That means that the production of mycotoxins in natural habitats is influenced by biotic and abiotic factors and could represent various toxin profiles and different concentrations of mycotoxins [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…These results show once again the need of investigating the effects of species interaction on mycotoxins synthesis, confirming what was seen similar to those reported by Müller et al . () where co‐cultivation of fungi in laboratory conditions influence each other metabolic profile.…”
Section: Discussionmentioning
confidence: 99%